Impact of Journaling on Students' Self-Efficacy and Locus of Control - Krista K. Fritson (Park University, 2008)
While considerable research has examined the academic and cognitive value of journaling, little has examined the psychological impact of journaling on the personal development of college students. Research on cognitive-behavior therapy indicates that journaling can have a positive impact on individuals' self-growth and intrapersonal characteristics. The purpose of this study is to examine the impact of classroom-based journaling on students' self-efficacy and locus of control. Students in two undergraduate courses were required to complete weekly journal assignments; one class received targeted information on cognitive-behavioral therapy (CBT) and one class did not. Students completed pre-, mid-, and post-course assessments on self-efficacy, locus of control, and learning. Results revealed that self-efficacy scores for both groups significantly improved after the early journaling assignments; however, there were no differences between those who received direct CBT instruction and those who did not. These findings indicate that journaling may have important psychological benefits above and beyond its expected academic and cognitive outcomes.